2007
DOI: 10.1002/jcb.21513
|View full text |Cite
|
Sign up to set email alerts
|

Secretion without Golgi

Abstract: A growing number of proteins devoid of signal peptides have been demonstrated to be released through the non-classical pathways independent of endoplasmic reticulum and Golgi. Among them are two potent proangiogenic cytokines FGF1 and IL1α. Stress-induced transmembrane translocation of these proteins requires the assembly of copper-dependent multiprotein release complexes. It involves the interaction of exported proteins with the acidic phospholipids of the inner leaflet of the cell membrane and membrane desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 167 publications
(266 reference statements)
4
142
0
1
Order By: Relevance
“…nonclassical secretory pathway [13][14][15][16]. Experimental studies suggested that FGF1 exhibited a physiologic profile that included a variety of metabolic responses.…”
Section: Methodsmentioning
confidence: 99%
“…nonclassical secretory pathway [13][14][15][16]. Experimental studies suggested that FGF1 exhibited a physiologic profile that included a variety of metabolic responses.…”
Section: Methodsmentioning
confidence: 99%
“…Nonclassical or leaderless secretion was first described 20 years ago for two mammalian proteins (Cooper and Barondes, 1990;Rubartelli et al, 1990) and since then considerable progress has been made in characterizing a number of different pathways (Fig. 2) in mammalian and yeast cells, which will not be described in detail here (for review, see Nombela et al, 2006;Nickel and Seedorf, 2008;Prudovsky et al, 2008;Nickel and Rabouille, 2009). It therefore seems likely that nonclassical secretion is common to all eukaryotes, including plants, although this field is essentially unexplored.…”
Section: How Do Proteins Reach the Plant Cell Wall?mentioning
confidence: 99%
“…However, several extracellular proteins such as IL1␣, IL1␤, fibroblast growth factor (FGF1 and FGF2), S100A13, sphingosine kinase 1, gelectin-1, and the extra vesicular p40 fragment of Syt1 all lack N-terminal signal sequences and are exported via ER-Golgi independent non-classical routes (10,(12)(13)(14). Most of these proteins are involved in several key biological functions, such as angiogenesis, cell proliferation or differentiation, and tumor growth.…”
mentioning
confidence: 99%